THE MEANING OF SINGGI PASSIKOLA IN THE KADA TOMINAA DISCOURSE FOR TORAJA COMMUNITIES - Anastasia Baan (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Singgi' passikola in Kada Tomina's discourse as one of the cultural assets contains messages that are meaningful to the Toraja people. This study used a qualitative approach to analyze the meaning of singgi' passikola utterances for the Toraja people. The research data was speech units in passikola singgi' obtained through interviews and speech recordings from Tomina. The research findings showed that the utterances of singgi passikola in the Kada Tomina discourse contain message meanings that have character values for Toraja people struggling to seek knowledge and who have completed their education. The message's meaning included enthusiasm in studying and working, being wise, adhering to God's teachings, having social concern, being humble, and having a stance. Therefore, singgi' passikola, as a part of cultural property, was also a vehicle for conveying educational messages to the Toraja people. The results of this study have significance for the preservation of the local culture of the Toraja people. In addition, the findings of this study can be a reference in developing the theory and discussion for further research. In the education context, these findings can be used as material for consideration in compiling a local content curriculum by utilizing local wisdom as a learning resource.